IoT-Enabled Smart Building Safety: Bibliometric Mapping and Validation of Research Readiness in Indonesia - Adwitya Bhaskara; Fitri Nugraheni; Sri Kusumadewi (JACEE (Journal of Advanced Civil and Environmental Engineering), 2025)
Building safety based on the Internet of Things (IoT) has become an increasingly important topic alongside the growing demand for smart building systems in Indonesia. This study aims to explore the direction of research development in this field and to assess the readiness of experts and practitioners for its implementation. The methods include a bibliometric analysis of international publications and a field survey using a questionnaire tested for validity and reliability. The validity test showed that 20 out of 23 items were valid, with an average correlation value of 0.56, while the reliability test obtained a Cronbach’s Alpha of 0.884, indicating a high level of internal consistency. The bibliometric and VOSviewer mapping results reveal that studies on IoT, smart buildings, and safety systems remain weakly interconnected, forming separate clusters with limited thematic overlap. In contrast, most respondents demonstrated a good level of understanding and readiness to adopt IoT-based safety technologies, although practical implementation is still limited to specific projects. Cost, policy, and human resource constraints remain the main barriers. Overall, the findings indicate that conceptual and professional readiness for IoT-based building safety is strong; however, its integration into practice remains insufficient, underscoring the need for closer collaboration among researchers, policymakers, and industry to accelerate the effective implementation of intelligent safety systems in Indonesia.